Gastrointestinal Adverse Effects of Elobixibat in Chronic Constipation: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Citra Safitri Wirman; Rudi Erwin Kurniawan; Darmawi; Benni Iskandar (Fakultas Farmasi Institut Kesehatan Medistra Lubuk Pakam, 2026)
Chronic constipation is a common gastrointestinal disorder that negatively affects quality of life and increases healthcare burden worldwide. Elobixibat, an ileal bile acid transporter inhibitor, has been introduced as a novel therapy to enhance intestinal fluid secretion and improve colonic motility in patients with chronic constipation. However, concerns remain regarding gastrointestinal adverse effects, particularly their potential relationship with dosage. Therefore, this study aimed to evaluate gastrointestinal adverse effects associated with elobixibat and to assess whether these events demonstrate a dose-dependent pattern. This systematic review and meta-analysis followed the PRISMA 2020 guidelines and was registered in PROSPERO (CRD420251155537). A literature search was conducted in PubMed and ScienceDirect to identify randomized controlled trials investigating elobixibat in chronic constipation patients published up to December 2025. Study eligibility was determined using the PICOS framework. Data on adverse effects, dosage, and treatment duration were extracted and analyzed using proportional meta-analysis with a random-effects model in R Studio, and risk of bias was assessed using the RoB2 tool. Five randomized controlled trials involving 922 participants are included in the analysis. The pooled proportion of diarrhea is 21%, abdominal distension is 26%, and abdominal pain is 16%, while unspecified gastrointestinal disorders represent the most frequently reported adverse events at 49%. Overall, gastrointestinal adverse events show a dose-dependent pattern, with higher doses associated with increased event rates. These findings indicate that elobixibat is associated with dose-dependent gastrointestinal adverse effects, highlighting the importance of individualized dosing and gradual titration to improve treatment tolerability.